LEVEL OF INFORMATION SECURITY AND ITS ROLE IN MODERN COMPUTER NETWORKS - Yuldashev Shohruhbek Zokirjon oglu; Mirzamakhmudov Azamatjon Bakhtiyor oglu (Galaxy International Interdisciplinary Research Journal, 2022)
The thesis discusses the role of information security in today’s modern computers and the development of measures to ensure information security in computer networks.